Making history in twentieth-century Quebec - Rudin, Ronald (Toronto ; Buffalo : University of Toronto Press, 1997)
"This book is the first comprehensive examination of the way in which French-speaking Quebecers have written about their past in the twentieth century. Rudin begins his study with Lionel Groulx, a professional historian who dominated the field for the first half of the century, and concludes with figures such as Paul-Andre Linteau who occupy an important place in the discipline today." "As a complementary volume to Carl Berger's The Writing of Canadian History, and as a new, critical reading of Quebec historiography, this book will stimulate considerable debate in the historical community."--Jacket
1. Not quite a profession: the historical community in early-twentieth-century Quebec -- 2. Nuts and bolts: Lionel Groulx and the trappings of a profession -- 3. The Maitre and his successors: the Montreal approach -- 4. Maybe it was our fault: the Laval approach -- 5. Searching for a normal Quebec: revisionism and beyond.
Includes bibliographical references (pages 273-285) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Québec (Province) -- Historiography; Historians -- Québec (Province); Historiens -- Québec (Province); Québec (Province) -- Historiographie; Canada -- Mœurs et coutumes -- Jusqu'à 1763.; HISTORY -- Canada -- General; Historians; Historiography; Québec; Geschichtsschreibung; Historiker; Québec; Geschiedschrijving; Geschichte 1900-1990.